Recurrent Cerebral Astroblastoma with Aggressive Histology: An Uncommon Case - Bansal, Sumit; Patra, Susama; Mishra, Pritinanda; Mahapatra, Ashok Kumar (Indian Journal of Neurosurgery, 2018)
Astroblastomas are uncommon tumors of uncertain histogenesis. Recently tanycyte is postulated to be the cell of origin. These occur predominantly in the cerebral hemisphere of young adults and children. Astroblastoma constitutes approximately 0.45 to 2.8% of all neuroglial tumors. We are reporting a case of 28-year-old woman who presented with headache and double vision. Magnetic resonance imaging (MRI) of the brain revealed well-demarcated, ring-enhancing solid cystic mass in right temporoparietal lobe with significant mass effect. The patient underwent gross total resection of the lesion through right temporoparietal craniotomy. The histopathologic diagnosis was suggestive of astroblastoma. She was advised for postoperative radiotherapy, but she lost to follow-up and again presented 1 year later with recurrent tumor in the same location along with another lesion in infratentorial location. She was reoperated and gross total excision of supra- and infratentorial tumor was done. She also received radiotherapy. We are reporting this uncommon case of astroblastoma and also reviewing the existing literature.
Keywords: astroblastoma; malignant; cystic